for an ap show that...?
show that ap + a(p+2) = 2a(p+1)
- SkywaveLv 77 years agoFavorite Answer
You have: ap + a(p + 2) = something.
So, removing brackets: ap + ap + 2a = that something,
i.e.: 2ap + 2a = that same something,
i.e.: 2a(p + 1) = that very same something.
But you asked us to show that:
ap + a(p+2) = 2a(p+1),
which by the above line of reasoning, has now been done!
Just out of curiosity, in what manner is your remark "for an ap" in your question relevant to this tiny sample of elementary algebra? :-/